Foucault in Iran - Sussan Siavoshi (International Institute of Islamic Thought, 2017)
To report history in the making, Michel Foucault travelled to Tehran in 1978. He had a commission from Corriere della sera, the prestigious Italian newspaper, to write a series of articles about the unfolding revolutionary process. He landed in Tehran two days after “Black Friday,” during which the army was believed to have massacred 5,000 people. Foucault was impressed by the courage of the undeterred protestors who kept pouring into the streets in defiance of a powerful regime. These articles, sympathetic to the movement and its leading force, Shi’a Islam, received a scornful response from his secular French colleagues. He was accused of being anti-modern, nihilistic, ignorant, and a man beguiled by a revolutionary effervescence. After the establishment of the Islamic Republic and the consequent bloody battles leading to the concentration of power in the hands of the militant religious revolutionaries, Foucault’s detractors put concerted public pressure upon him to repent for his “mistaken” judgments. This major “French” controversy failed, however, to attract much attention in English-speaking circles until the appearance of Janet Afary and Kevin Anderson’s Foucault and Iranian Revolution: Gender and Seduction of Islamism (University of Chicago Press: 2005). Highly critical of Foucault’s “romantic” depiction of the revolutionary movement, these two authors also found in his reports an occasion to attack his early, post-structuralist writings, interpreting them as anti-modern. The book’s overt critique of Foucault rested upon the intellectual pillar of the Enlightenment discourse, with its teleological and secularist approach to history. Needless to say, Afary and Anderson were also critical of Islam’s public role, not only in the revolution but also beyond ...